CAN MYTHS, RITUALS, AND MAGIC INCREASE SELF-EFFICACY AND CONSUMER BEHAVIOR FOR INCREASING A HEALTHY LIFESTYLE? - Ubud, Sahnaz; Santoso, Vina Valencia (Universitas Brawijaya, Indonesia, 2023)
Nowadays, the healthy lifestyle of modern society has increased. However, modern society still considers myths, rituals, and magic to improve their healthy lifestyle. This study aims to discover how myths, rituals, and magic, which are part of the consumer behavior culture, increase self-efficacy and healthy lifestyle behavior in modern society. This research used a qualitative approach based on consumer behavior and self-efficacy in the healthy lifestyle for breastfeeding mothers. In-depth interviews were conducted to determine the self-efficacy among eleven breastfeeding mothers in improving a healthy lifestyle. The coding process for all participants used NVivo to analyze the interviews' results. The interviews indicated that most informants still believe in myths, rituals, and magic about breastfeeding mothers. It indicates that Indonesians having a solid culture, still believe that myths, rituals, and magic could be considered in increasing self-efficacy and healthy lifestyle behavior. So, a healthy lifestyle is currently a significant concern in the community, especially during the Covid-19 pandemic. Covid-19 has changed many routines in ways that no one could anticipate so that it can reduce the community's healthy lifestyle, especially for breastfeeding mothers. Indonesian, who currently live in the millennial era, still consider that culture as one of the considerations in improving healthy living behavior. Further research should consider how the sustainability of healthy lifestyle behavior is seen from social capital through knowledge mechanisms regarding current healthy environmental issues and consumer involvement in the environment. In addition, paying attention to ethics and ethnicity in society is crucial in discussing community culture, especially when considering consumers' healthy lifestyles.